Intermediate and Long-term Outcomes of Mitomycin C–enhanced Trabeculectomy as a First Glaucoma Procedure in Uveitic Glaucoma. Issue 5 (May 2017) - Almobarak, Faisal A.; Alharbi, Ali H.; Morales, Jose; Aljadaan, Ibrahim
Abstract : Objectives: To evaluate the intermediate and long-term outcomes of mitomycin C–enhanced trabeculectomy as a first glaucoma procedure in uveitic glaucoma. Materials and Methods: Retrospective cohort study included 70 eyes of 50 patients with uveitic glaucoma who underwent mitomycin C–enhanced trabeculectomy as a first glaucoma procedure at King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia between 1996 and 2014. The main outcome measures were: the intraocular pressure (IOP), the number of antiglaucoma medications, the presence of visually threatening complications, and the need for further surgeries to control the IOP. Surgical outcome of each eye was classified as an absolute success, qualified success, or failure, based on the main outcome measures. Results: The mean follow-up period was 77.0 months (±40.9). The IOP and number of antiglaucoma medications decreased significantly from a mean of 39.5 mm Hg (±8.9) and 3.7 (±0.8) to 14.4 mm Hg (±6.9) and 1 (±1.3) at the last follow-up, respectively ( P <0.001 for both). The cumulative probabilities of success were 60% and 35.7% at 36 and 60 months postoperatively, respectively. The most common complications were cataract development and progression (45.3%), hypotony (IOP ⩽5 mm Hg) (30%) and IOP spike≥30 mm Hg (10%). Eighteen eyes (25.7%) needed a second procedure to control the IOP. Conclusions: Although mitomycin C–enhanced trabeculectomy offers reasonable intermediate and long-term IOP control and safety in uveitic glaucoma, a significant number of patients needed further procedures to control the pressure. Thus, continuous monitoring of the pressure and inflammation are crucial.